Magnetic Biofilm Carriers: The Use of Novel Magnetic Foam Glass Particles in Anaerobic Digestion of Sugar Beet Silage - Ramm, Patrice; Jost, Carsten; Neitmann, Elisabeth; Sohling, Ulrich; Menhorn, Oliver; Weinberger, Karl; Mumme, Jan; Linke, Bernd (Journal of Renewable Energy, 2014)
The use of recently developed magnetic foam glass particles for immobilization of microbial biomass was tested. The effect of the particles was illustrated at the production of biogas from sugar beet silage as the sole substrate. Lab-scale fermentation experiments were conducted using a mesophilic completely stirred tank reactor and a magnetic separator. Microscopic analysis revealed biofilm coverage of 50–60% on the surface of the particles within 110 days. It was possible to recover 76.3% of the particles from fermentation effluent by means of a separation procedure based on magnetic forces. Comparing a particle charged reactor with a control reactor showed a small performance gain. The methane rate was increased from 1.18±0.09 to 1.25±0.06 L L−1 d−1 and the methane yield was increased from 0.302±0.029 to 0.318±0.022 L g−1 (volatile solids) at an organic loading rate of 3.93±0.22 g L−1 d−1 (volatile solids). Maximum methane rates of 1.42 L L−1 d−1 at an organic loading rate of 4.60 g (volatile solids) L−1 d−1 (reactor including magnetic particles) and 1.34 L L−1 d−1 at 3.73 g L−1 d−1 (control reactor) were achieved. Based on the results, it can be concluded that the use of magnetic particles could be an attractive option for the optimization of biogas production.